PHLEOMORPHIC ADENOMA (BENIGN MIXED TUMOR) PADA PALATUM MOLLE (LAPORAN KASUS) - Sigit Supartono; Dwiyanto Dwiyanto; Chusnul Chotimah (Faculty of Dentistry, Universitas Indonesia, 2015)
Phleomorphic adenoma is the most commonly found tumor of the salivary glands. This tumor is usually found in the postero-lateral region of the hard palate. In this case, a phelomorphic adenoma situated in the oropharynx region was reported. The CT-Scan results showed an expansive and infiltrative appearance, suspected to be a malignancy, where wide excision was previously planned to be carried out. During surgery, the mass was found pedunculated in the soft palate. It was then decided to perform an exicision as the choice of therapy.